2016
DOI: 10.1016/j.eururo.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery Pathways Versus Standard Care After Cystectomy: A Meta-analysis of the Effect on Perioperative Outcomes

Abstract: Context Enhanced recovery after surgery (ERAS) protocols aim to improve surgical outcomes by reducing variation in perioperative best practices. However, among published studies, results show a striking variation in the effect of ERAS pathways on perioperative outcomes after cystectomy. Objective To perform a systematic review of the literature and a meta-analysis comparing the effectiveness of ERAS versus standard care on perioperative outcomes after cystectomy. Evidence acquisition We performed a literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(123 citation statements)
references
References 28 publications
4
106
0
13
Order By: Relevance
“…28,35,44,45 A recent meta-analysis by Tyson and Chang found no significant difference in overall readmissions or 90-day mortality through ERAS implementation though a lower complication rate was noted (39.6% with ERAS vs 51.5% with standard care). 46 The same analysis also found a mean decrease in length of stay with ERAS of greater than 5 days along with a 1 day faster return of bowel function. 46 potential indicator of quality.…”
Section: Evidence-based Components Of Eras In Radical Cystectomymentioning
confidence: 71%
See 2 more Smart Citations
“…28,35,44,45 A recent meta-analysis by Tyson and Chang found no significant difference in overall readmissions or 90-day mortality through ERAS implementation though a lower complication rate was noted (39.6% with ERAS vs 51.5% with standard care). 46 The same analysis also found a mean decrease in length of stay with ERAS of greater than 5 days along with a 1 day faster return of bowel function. 46 potential indicator of quality.…”
Section: Evidence-based Components Of Eras In Radical Cystectomymentioning
confidence: 71%
“…Additional groups have reported experiences with various ERAS protocols demonstrating consistently shorter time to regular diet, time to return of bowel function, and length of hospitalization . A recent meta‐analysis by Tyson and Chang found no significant difference in overall readmissions or 90‐day mortality through ERAS implementation though a lower complication rate was noted (39.6% with ERAS vs 51.5% with standard care) . The same analysis also found a mean decrease in length of stay with ERAS of greater than 5 days along with a 1 day faster return of bowel function .…”
Section: Radical Cystectomymentioning
confidence: 95%
See 1 more Smart Citation
“…Minimally invasive surgery has been added as one of the 22 elements of ERP thus, robotic surgeons try to apply ERP, but the fact remains that it is underutilized. ERP has shown that it decreases LOS, postoperative ileus, complications and risk for readmission at 30 days …”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…ERP has shown that it decreases LOS, postoperative ileus, complications and risk for readmission at 30 days. 15 Having said this, we understand beforehand, that the absence of ERP and the intracorporeal approach might introduce bias and create problems in the interpretation of the results. If not all, many studies including all published RCTs, did not use the totally intracorporeal approach, did not describe thoroughly their clinical pathway or the use of ERP and in many cases, the diversion commonly used is the ileal conduit and not the neobladder.…”
Section: Perioperative Outcomesmentioning
confidence: 99%